TWO HALF OF A SAME BARREL: POTENCIALITIES AND LIMITATIONS OF HAPTIC DRAWINGS - Lillo Jover, Julio (Anales de Psicología / Annals of Psychology)
After defining what raised-line drawings are, describing their differential features with respect to other tangible graphics and their complementary utilities to braille, a critical evaluation is made taking into consideration both the factors that limit their effectiveness (the empty half of the barrel) and the factor that promote it (the full half of the barrel). At the end, this paper aims to specifying how to make a productive usage of this kind of material.